MEMBRAN KULIT TELUR SEBAGAI BIOSENSORASAM URAT SEDERHANA, STABIL, DAN RAMAH LINGKUNGAN - Rani, Ismarani (CEFARS : JURNAL AGRIBISNIS DAN PENGEMBANGAN WILAYAH, 2012)
Utilization ofeggshellmembraneasa biosensorbeing developedbyseveralresearchbecause it hasmany advantages. The resultingbiosensorlatestresearchcan still producea sensitivity of89% andgood stabilitycan be up tothreemonthswhenstoredat 4 ° C. The biosensormeasurementswithverygoodtomeasureuricacidinhumanserumandurine. These biosensorsare verysimple, does notrequirea huge cost, stableandenvironmentallyfriendly.